Consequence of Indoor Air Pollution in Rural Area of Nepal: A Simplified Measurement Approach - Ranabhat, Chhabi Lal; Kim, Chun-Bae; Kim, Chang-Soo; Jha, Nilambar; Deepak, K. C.; Connel, Fredric A. (Frontiers in Public Health, 2015)
People of developing countries especially from rural area are commonly exposed to high levels of household pollution for 3–7 h daily using biomass in their kitchen. Such biomass produces harmful smoke and makes indoor air pollution (IAP). Community-based cross-sectional study was performed to identify effects of IAP by simplified measurement approach in Sunsari District of Nepal. Representative samples of 157 housewives from household, involving more than 5 years in kitchen were included by cluster sampling. Data were analyzed by SPSS and logistic regression was applied for the statistical test. Most (87.3%) housewives used biomass as a cooking fuel. Tearing of eyes, difficulty in breathing, and productive cough were the main reported health problems and traditional mud stoves and use of unrefined biomass were statistically significant (p < 0.05) and more risk (AOR > 2) with health problems related to IAP. The treatment cost and episodes of acute respiratory infection was >2 folders higher in severe IAP than mild IAP. Simplified measurement approach could be helpful to measure IAP in rural area. Some effective intervention is suggested to reduce the severe level of IAP considering women and children.